Implementasi Metode Qiro’ati Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Pada Anak Kelas Ii Di Madrasah Ibtidaiyah Asy-Syafi’iyyah Karangpapak Sukabumi - Alinda Nur Maulidatsani; M. Kholil Nawawi; M. Azhar Alwahid (KOLONI, 2024)
This research was motivated by several problems that occurred in Al-Qur'an learning activities at Madrasah Ibtidaiyyah Asy-Syafi'iyyah Karangpapak. Madrasah Ibtidaiyyah Asy-Syafi'iyyah Karangpapak is a primary level educational institution that uses the Qiro'ati method as a way to improve its students' ability to study and read the Al-Qur'an properly and correctly. The Qiro'ati method is a practical method and makes it easy to study the Al-Qur'an quickly and precisely. The aim of this research is to determine the implementation of the Qiro'ati method applied by MI Asy-Syafi'iyyah Karangpapak in studying the Al-Qur'an. This research uses a qualitative method with a descriptive approach. This approach is useful for obtaining data that actually occurs in the field when conducting research. Data collection techniques use observation, interviews and documentation methods. The data validity test used is data triangulation. The results of the research that has been carried out are that this method can improve students' ability to read the Al-Qur'an well, although the changes are not significant. The supporting factors for this program are competent teachers and students who quickly grasp the learning, as well as adequate infrastructure. Meanwhile, the inhibiting factors are the students' different abilities and are sometimes difficult to manage, as well as the lack of support from the students' parents.